The Role of Ionic Liquid Interaction in the Separation of Fatty Acid Methyl Esters—Polyunsaturated Geometric Isomers in GC–MS - Emerencia Mező; Anita Bufa; Csilla Páger; Viktória Poór; Tamás Marosvölgyi; Ferenc Kilár; Lilla Makszin (Separations, 2021)
Knowledge of the type and level of saturated and unsaturated fatty acids in food and clinical matrices is of practical importance, but the wide variety of fatty acids makes analyses very complex. The discrimination of the geometric isomers of fatty acid needs proper and effective separation conditions. The efficiency of three different stationary phases was evaluated by GC–MS methods in the separation of fatty acids in their methyl ester forms. Significant differences were observed in the efficiencies of polysiloxane-based (non-polar HP-5MS and medium/high polarity DB-225MS) and ionic liquid-based (SLB-IL111) columns. Baseline separation of the geometric isomers of linoleic acid methyl ester was obtained by the extremely polar SLB-IL111 column, showing a preference over the other two columns. The optimization of the experimental conditions (response linearity, limit of detection, limit of quantification, system suitability, intraday and interday repeatability and accuracy) showed the separation power of the ionic liquid interaction in the analyses by using short (25–30 m long) columns. By deducting the general principles of the interaction, predictions can be made for the separation of other isomers. The results facilitate the precise identification of various types of fatty acids in real samples for nutritional information.